Alternative fuzzy C-Means clustering for DNA computing readout method implemented on DNA engine opticon 2 system - Muhammad Faiz Mohamed Saaid, 1984-, author; Zuwairie Ibrahim, author; Marzuki Khalid, author; Azli Yahya, author; International Conference on Signal-Image Technology & Internet-Based Systems (4th: 2008: Bali, Indonesia) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL